Implementation of stubble in agricultural production: A review (Agro Productividad, 2022)
Objective: To elucidate the benefits that agricultural residues or stubble have in agricultural activities, through a bibliographic and objective review that could help to make the actors of agricultural sector aware of the benefits and their correct implementation in production systems.Design/methodology/approach: A detailed review of scientific articles from the main academic databases and repositories was performed. We took into account aspects such as the use of stubble as plant cover; effects and changes in physical and chemical structure of soil; crop yield and use for livestock feeding.Results: The use of stubble has beneficial effects on agricultural activities. In agriculture, they have positive effects for the proliferation of beneficial organisms and assimilation of nutrients, which are easily absorbed by plants. Consequently, crop yield is maximized both in quantity and quality terms. In livestock sector, the stubble implement provides nutrients such as proteins, ashes and vitamins, which together with conventional diets, reduce production costs and improve meat and milk production.Limitations on study/implications: The repertoire of scientific articles related to stubble is very broad, making it difficult to assimilate the information. In Mexico, particularly, more research is needed to inform farmers of the possible uses of stubble.Findings/conclusions: The use of stubble in agricultural activities generates benefits at ecological and economic levels, which ensure the sustainability and resilience of agroecosystems. Nutritional content of stubble is a function of the species and/or varieties of agricultural species. The lack of knowledge in the management of stubble leads to these being incinerated, releasing particles and toxic and polluting substances for the environment, further favoring the conditions for greenhouse effect.